Gaps in seed banking are compromising the GSPC’s Target 8 in a megadiverse country - Teixido, Alberto L.; Toorop, Peter E.; Liu, Udayangani; Ribeiro, Guilherme V. T.; Fuzessy, Lisieux F.; Guerra, Tadeu J.; Silveira, Fernando A. O. (Biodiversity and conservation, 2017)
Ex situ seed conservation is an effective strategy to help safeguarding plants from extinction. The updated Global Strategy for Plant Conservation’s (GSPC) Target 8 aims to include 75% of threatened plant species in ex situ collections by 2020, preferably in the country of origin. Halfway through the updated GSPC program, we evaluate the current state of knowledge and practice of ex situ seed conservation of threatened species from megadiverse Brazilian flora, contributing to this Target. We identify knowledge gaps and costs to achieve Target 8 through seed banking in Brazil within the time constraints of the GSPC and in a scenario of recent science budget funding cuts. Knowledge on seed storage behavior is available only for 24 Brazilian species (1.3%). Seed desiccation tolerance was concluded for 175 of 228 species, feasibly allowing safe storage of most Brazilian species at sub-zero temperatures. However, only 26 species (1.3%) are effectively banked in research institutions. Surprisingly, the percentage of banked threatened species hardly increased in the first 5 years since the update of the Target (0.55%, 2011–2015), and Brazil now faces the challenge of banking almost 1500 species during 2016–2020. Despite a major lack of commitment of Brazilian institutions and of knowledge to achieve the Target, the costs for banking the remaining species were estimated to be only US$3.9 million. We call for a nationwide coordinated effort of government agencies, policy makers and research institutions to include ex situ seed conservation in the environmental agenda to pursue achievement of the Target by 2020.